2000
DOI: 10.1103/physrevlett.84.2160
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Rod-Coil Multiblock Copolymers and the Effect of the Helix-Coil Transition

Abstract: The extension elasticity of rod-coil mutliblock copolymers is analyzed for two experimentally accessible situations. In the quenched case, when the architecture is fixed by the synthesis, the force law is distinguished by a sharp change in the slope. In the annealed case, where interconversion between rod and coil states is possible, the resulting force law is sigmoid with a pronounced plateau. This last case is realized, for example, when homopolypeptides capable of undergoing a helix-coil transition are exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 20 publications
2
83
0
Order By: Relevance
“…They have explicitly added extension force into the Zimm and Bragg description. In one of their papers a step-like behavior of helicity degree versus normalised force has been reported [60], without any model for solvent. A thorough study of Tamashiro and Pincus reported no step-like behavoir of helicity degree within the same model [61].…”
Section: E Pressure Versus Force: What Is the Difference?mentioning
confidence: 99%
“…They have explicitly added extension force into the Zimm and Bragg description. In one of their papers a step-like behavior of helicity degree versus normalised force has been reported [60], without any model for solvent. A thorough study of Tamashiro and Pincus reported no step-like behavoir of helicity degree within the same model [61].…”
Section: E Pressure Versus Force: What Is the Difference?mentioning
confidence: 99%
“…In the following, we assume, as in [30], that the penalizing term J dominates this effect, so that we always consider single folded domain configurations (thus we assume n b f ¼ 1: di-block approximation). This hypothesis is supported by the MD simulations [22] showing an unfolding strategy with always one single connected internal unfolded domain inside two boundary-folded domains.…”
Section: Energetic Assumptionsmentioning
confidence: 99%
“…Here, Q is the unfolding energy for a single domain and J is a penalizing 'interfacial' energy term (measuring the loss of internal energy owing to the unbind terminal hydrogen bonds of each contiguous folded domain [30]). …”
Section: Energetic Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations